SYNTHESIS, CHARACTERIZATION AND STABILITY CONSTANT STUDY OF TRANSITION METAL COMPLEXES OF CHLOROQUINE PHOSPHATE (CAHIERS MAGELLANES-NS, 2024)
This chapter discusses the chloroquine phosphate. The chemical name of chloroquine phosphate in chemical abstracts is found under the heading Quinoline and designated as 7-Chloro- [4-(4-diethylamino-1-methylbutylamino)] quinoline diphosphate. Chloroquine phosphate is a white, odorless, crystalline powder having a bitter taste: it discolors gradually on exposure to light. pH-metric studies of complexes of Co(II), Cu(II), Ni(II) & Zn(II) with Cloroquine phosphate were carried out in aqueous solution and in solid state. Change in potential value suggesting the formation of complex. To calculate the stability constant for binary complexes, Irvin-Rosotti method were used. IR spectra, elemental analysis and Melting point of the complexes indicates the formation of complexes in solid state.